Description of the scientific domain Macrobrachium through the analysis of the authors with higher productivity and higher H-index according to Scopus - Chong-Carrillo, Olimpia; Moraes-Valenti, Patricia [UNESP]; Vega-Villasante, Fernando; Chavez-Chong, Cristina O.; Arencibia-Jorge, Ricardo; Michan-Aguirre, Layla (Univ Catolica De Valparaiso, 2018)
One of the most important domains in aquaculture is Macrobrachium, since it represents one of the most cultured crustacean genus worldwide. Description of the authors that study and publish on the subject constitutes a solid contribution to the knowledge of this genus. Indicators of productivity, visibility, relevance, sex and co-authorship of the authors were collected from the Scopus database for the period 1980-2016 to describe the Macrobrachium domain. Conceptual mapping techniques were used to visualize co-author relationships. The greatest amount of contributions to knowledge of the genus Macrobrachium was shown to come from researchers in China, Brazil, USA and India. Only seven women are among the most productive and relevant authors. Multiple co-author networks exist in which the most relevant researchers are the center. Many networks appear to be closed groups with little interaction between external groups or researchers.
Keywords: Macrobrachium; scientific production; co-author networks; functional principal components analysis